Risk Mitigation and Food Security in the Free Nutritious Food Program: Implications for National Defense - Saputro, Sukoco Henry; Sarjito, Aris; Duarte, Editha Praditya (PT FORMOSA CENDEKIA GLOBAL, 2025)
This article analyzes risk mitigation in the implementation of the Free Nutritious Food Program (MBG) in Indonesia, focusing on its impact on food security and national defense, particularly from a non-military defense perspective. The program aims to improve the nutritional quality of the community through guaranteed distribution of nutritious food, but faces challenges related to operational, financial, governance and oversight risks. A desk-based exploratory qualitative approach was used to explore the ISO 31000:2018 risk management framework, and assess and manage these risks in the context of the MBG. The findings show that the success of the MBG is highly dependent on strengthening distribution infrastructure, transparency in budget management and inter-agency coordination. Dependence on food imports threatens domestic food security and social stability, making it an integral part of national defense. Source triangulation and thematic analysis were used to ensure the validity and credibility of the findings. The research suggests integrated mitigation measures, including surveillance technology and strengthening domestic food security, as key to program sustainability and state stability.